2014
DOI: 10.1007/s10753-014-0067-z
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate Ameliorates Functional Limitations in Freund’s Complete Adjuvant-Induced Monoarthritis in Rat by Maintaining Oxidative Homeostasis and Inhibiting COX-2 Expression

Abstract: Drugs exhibiting anti-inflammatory and analgesic properties have been clinically used in the management of pain and impairment of joint functions in arthritis. In view of available studies on the beneficial effect of artesunate in various inflammatory conditions, the present study was carried out to evaluate its efficacy in ameliorating functional limitations of arthritis and to understand the underlying mechanisms. The study was carried out in rat model of Freund's complete adjuvant-induced monoarthritis wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 43 publications
(43 reference statements)
0
25
0
Order By: Relevance
“…Despite its high effi cacy in vaccination, FCA has adverse effect and application of FCA is connected with an unwanted distress (1). Firstly, application of FCA causes pro-infl ammatory reaction of immune system with growing infl ammatory cytokines release (2,3). Several adverse effects by FCA application can arise as a result of infl ammation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high effi cacy in vaccination, FCA has adverse effect and application of FCA is connected with an unwanted distress (1). Firstly, application of FCA causes pro-infl ammatory reaction of immune system with growing infl ammatory cytokines release (2,3). Several adverse effects by FCA application can arise as a result of infl ammation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it can inhibit the degradation of type II collagen degradation, may have a certain effect on arthritis, bone osteoporosis, and other diseases [17]. Elevation of COX-II expression appeared in the rats of OA was also suppressed following treatment with artesunate [35]. In addition, it has been reported that Viatril-S has anti-inflammatory properties by contributing to inhibit COX-II [20].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that Art presents a beneficial effect on the treatment of experimental arthritis models . For instance, Art treatment initiating in the induction phase of collagen‐induced arthritis (CIA) promoted a significant amelioration in the inflammatory process of the cartilages and that effect correlated with a diminished infiltration of leukocytes to the joints . Art treatment in CIA promoted a reduction in the serum levels of TNF‐α and the chemotactic factor MCP‐1 .…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that Art has little effect on the activation of T cells and dendritic cells. Literature present data regarding alterations in macrophages, synoviocytes, and B lymphocytes followed Art treatment . We did not evaluate these cellular components in our study, as EAE is mainly a T cell‐driven disease, although macrophages play an important role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation